2013
DOI: 10.3174/ajnr.a3575
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Morphologic and Hemodynamic Parameters for Unruptured Posterior Communicating Artery Aneurysms with Oculomotor Nerve Palsy

Abstract: BACKGROUND AND PURPOSE:Posterior communicating artery aneurysms with oculomotor nerve palsy may imply sudden enlargement of the aneurysm sac and have a high risk of rupture. Our aim was to identify the morphologic and hemodynamic parameters in this special period of aneurysm progression and to assess related rupture risk indices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In a previous hemodynamic study on mirror PcomA aneurysms, we also showed that, compared with unruptured aneurysms, ruptured aneurysms have a lower WSS and a larger low WSS area 4. In another study11 we observed that unruptured PcomA aneurysms with oculomotor nerve palsy have lower WSS than ruptured aneurysms. Hence, oculomotor nerve palsy is a clinical symptom of the sudden increase in the PcomA aneurysm sac, and PcomA aneurysms with oculomotor nerve palsy have a higher risk of rupture.…”
Section: Discussionsupporting
confidence: 50%
“…In a previous hemodynamic study on mirror PcomA aneurysms, we also showed that, compared with unruptured aneurysms, ruptured aneurysms have a lower WSS and a larger low WSS area 4. In another study11 we observed that unruptured PcomA aneurysms with oculomotor nerve palsy have lower WSS than ruptured aneurysms. Hence, oculomotor nerve palsy is a clinical symptom of the sudden increase in the PcomA aneurysm sac, and PcomA aneurysms with oculomotor nerve palsy have a higher risk of rupture.…”
Section: Discussionsupporting
confidence: 50%
“…Researchers performed morphological–hemodynamic analysis on matched pairs of ruptured/unruptured mirror or symptomatic PCoA aneurysms and found correlations between some hemodynamic factors and PCoA aneurysm rupture 12 13. This is encouraging and promising, but the findings are limited by very small sample sizes and lack of analysis of clinical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…More and more published CFD studies seem to suggest that high WSS results in intracranial aneurysm growth and low WSS in rupture. 7,12,14,15,18,19,22,24,25,27 However, these results were inconsistent with those obtained by Liu et al and Yu et al 13,26,30,34 They found high WSS in the ruptured aneurysm group. Moreover, it is important to note that their average WSS in the aneurysm region (1.64 ± 1.16 N/m 2 ) was significantly lower than that observed in the vessel region (p < 0.05), which highly accords with our findings.…”
Section: Discussionmentioning
confidence: 70%